Guidelines for radiation therapy for endometrial cancer by Brachytherapy Committee of China Anti-Cancer Association (V 2025.1) - Xinping Cao; Xiugui Sheng; Yijing Ye; Renjia Shu; Fuquan Zhang; Xin Lei; Zhihua Sun; Lichun Wei; Hanmei Lou; Shuxia Cheng; Fang He; Yi Ouyang; et al. (Holistic Integrative Oncology)
Abstract Endometrial cancer (EC) is the sixth most common cancer in women worldwide, with an increasing incidence rate in China. Radiotherapy (RT) is important for the treatment of EC, especially for high risk or advanced stage tumors. The Brachytherapy Committee of China Anti-Cancer Association (CACA) organized relevant experts to develop this guideline and provide evidence-based RT recommendations tailored to China’s epidemiological and clinical landscape. Highlighting key updates in molecular subtyping and the revised 2023 FIGO staging system, this portion of the CACA Guidelines for EC emphasizes personalized strategies across disease stages and details protocols for postoperative settings (radical resection, incomplete staging), recurrent/metastatic disease, and palliative care. By consolidating contemporary practices and regional data, this framework aims to standardize RT delivery, and improve survival outcomes while minimizing toxicities. We hope that this guideline will provide effective references for radiation oncologists, so as to achieve the best radiation treatment effects for EC patients in China.